The Novo Progresso Formation, Tapajós Gold Province, Amazonian Craton: zircon U-Pb and Lu-Hf constraints on the maximum depositional age, reconnaissance provenance study, and tectonic implications - KLEIN, Evandro Luiz (2018)
The Novo Progresso Formation, located in southeastern Tapajós Gold Province, at its boundary with the Iriri-Xingu Domain, south of the Amazonian Craton, is composed of quartz- and lithic-arenites and siltstones with volcanic/volcanoclastic contributions, and was deposited in fluvial and lake systems. Reconnaissance detrital zircon U-Pb LA-ICP-MS data on a lithic arenite indicate maximum depositional age around 1840 Ma, whereas structural relationships suggest a minimum age of 1780 Ma. The zircon age spectrum shows two well-defined peaks at 1846 and 1968 Ma, and statistically secondary peaks ranging from 2185 Ma to 2973 Ma. εHf values vary from +8.1 to -14.5 (TDM = 2.13 to 3.95 Ga), whereas the εNd values range from -2.5 to -3.3 (TDM = 2.31 to 3.21 Ga), with one positive value of +4.5 (TDM = 1.81 Ga). These data and the lithological composition indicate that surrounding Orosirian rocks from Tapajós and Iriri-Xingu were the main sources for the sediments, with subordinate contributions from older and more distant domains of the Amazonian Craton. In addition, the Hf systematics suggest a ~2.50 Ga-old crustal growth event and a ~3.95 Ga-old hidden component in the eastern portion of the Amazonian Craton. The deposition of the Novo Progresso Formation is related to the development of the large Orosirian intracra-tonic rift system known as Uatumã Silicic Large Igneous Province (1.89-1.80 Ga), which cut across the Amazonian Craton, following the final stages of magmatism in the Tapajós Gold Province.